Representation of Lord Shiva as Man in Amish Tripathi’s Shiva Trilogy - G. Sharmely (The Creative Launcher, 2016)
More recently, in Indian Writing in English several mythological tales are getting a modern makeover into historical fictional themes. Amish Tripathi’s Shiva Trilogy is a fantasy re-imagining of the Indian deity Lord Shiva’s life and adventures. The trilogy also portrays how Gods were human beings ages ago until they attained immortality as a result of their deeds and actions. This paper analyzes how Amish has represented Lord Shiva as a man who rose Godlike because of his karma, inspite of the Hindu mythology referring him as a God, ‘The Mahadev’. Amish in Shiva Trilogy attempts to humanize the Hindu eternal ‘Mahadev’ - The God of Gods and the destroyer of evil with knowledge as its underlying theory.